(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The evolution of music education, particularly in higher education, has seen significant shifts due to advancements in digital technologies. This article explores various methodological approaches to teaching music in higher education and how these can be enhanced through the integration of digital tools. It addresses traditional pedagogical models, modern approaches, and the potential for digital technologies to enrich teaching practices and learning experiences. The paper further examines the impact of technologies on students’ creativity, critical thinking, and engagement. It also discusses the challenges and opportunities posed by this integration and suggests recommendations for future educational practices in music.